Heat delays skin wound healing in mice - dos Santos-Silva, Marco Aurélio; Trajano, Eduardo Tavares Lima; Schanuel, Fernanda Seabra; Monte-Alto-Costa, Andréa (Experimental biology and medicine (Maywood, N.J.), 2017)
In vivo studies have shown that the combination of infrared radiation (IR) and visible light (VIS) is responsible for the activation of metaloproteinases, causing matrix degradation and damage to healthy skin. However, the role of heat originating from the VIS spectrum on wound healing remains poorly understood. Our objective was to investigate the macroscopic, microscopic and biochemical effects of heat induced by visible light on cutaneous wound healing in mice. Male mice were anesthetized, subjected to a cutaneous excisional wound and divided into two groups (n = 10/group) exposed to 23℃ or 43℃ in a thermal chamber for 30 min every other day, for 13 days. On day 14, the animals were sacrificed, and their lesions were processed for histochemistry, immunohistochemistry and protein expression analysis. The wound area was 42% greater 11 days (p < 0.01) and 29% greater 14 days (p < 0.001) after wounding in the 43℃ group than in the 23℃ group. The 43℃ group presented a lower (17%) percentage of reepithelialized wounds (p < 0.001) 14 days after wounding. The length of the epidermal gap was greater in the 43℃ group (p < 0.01). The volume density of myofibroblasts and the number of F4/80-positive macrophages was greater in the 43℃ group (p < 0.05). The 43℃ group showed increased protein expression of type III collagen (p < 0.001), decreased protein expression of type I collagen (p < 0.05), increased MMP-1 expression (p < 0.05), and decreased MMP-2 activity (p < 0.001). The protein expression of fibrillin-1 (p < 0.001), MMP-12 (p < 0.05), TGF-β 1/2/3 (p < 0.01) and ERK activation (p < 0.05) was increased in the 43℃ group. Our results suggest that heat delays the stages of wound healing in mice.